Jenis Dan Pengaruh Keberadaan Alga Filamen Pada Kegiatan Budidaya Eucheuma cottonii Di Perairan Teluk Kotania, Seram Bagian Barat, Maluku (The Effect of the Existence of Filament Algae on Eucheuma Cottonii Cultivation Activity in Kotania Gulf Waters, West Seram, Maluku) - Wahyu Purbiantoro; Wida Lesmana; Hairarti Arfah (IPB University, 2013)
The success of Eucheuma cottonii cultivation in the Gulf Kotania, West Seram, Maluku was influenced by various factors, one of them was the existence of filament algae. This study aims to identify filament algae patching on the thalus E. cottonii, the influence of filament algae biomass on specific growth rate (SGR) of E. cottonii in trial raft and the differences of filament algae biomass patching on the thalus E. cottonii cultivated by local people in three different locations. The first study was conducted in trial raft, then the identifications and measurements of filament algae biomass patching on the thalus and the measurements of E. cottonii biomass were performed on day 34 and 50. In the second study, the identifications and measurements of filament algae biomass patching on the thalus E. cottonii has been done on the three difference locations where E. cottonii has been cultivated by local people. The results showed that Lyngbia sp. was a species of filament algae found in thalus E. cottonii in which the algae patch on. The presence of filament algae on the thalus with biomass ratio 1:81, did not affect significantly on SGR of E. cottonii in trial raft. Meanwhile, filament algae biomass obtained from three different locations showed a significant difference, where the filament algae biomass in Wael Village was the highest.Keywords: Filament Alga, Lyngbia sp., Eucheuma cottonii, Gulf Kotania